Endoscopic treatment of leak at the tip of the “J” ileal pouch - Kochhar, Gursimran Singh; Shen, Bo (Endoscopy International Open, 2017)
Background and study aims The tip of the “J” of the ileal pouch is the vulnerable location for leak after restorative proctocolectomy, which has normally been treated with surgery. We aimed to describe a novel endoscopic method to treat the same. Patients and methods A cohort of 12 consecutive patients with a leak at the tip of the “J” was identified in our prospectively maintained Pouch Registry. The endoscopic over-the-scope clipping (OTSC) system was used for the closure of the leak. Results Eight patients (66.6 %) achieved complete closure of the leak documented by endoscopy confirmed with guidewire and/or contrasted pouchogram, with 6 requiring a single endoscopic session and 2 undergoing a repeat session. Four patients (33.3 %) had a persistent leak and required surgical intervention, of whom 1 developed abscess in the pre-spine region 14 days after the endoscopic procedure and underwent pouch revision surgery.Conclusions OSTC appears to be safe and effective in treating the leak at the tip of the “J” in the majority of patients.